2023
DOI: 10.3390/microorganisms11071633
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Plant Microbiota under Conventional and Organic Fertilization Regimes in a Soilless Culture System

Carolina N. Resendiz-Nava,
Fernando Alonso-Onofre,
Hilda V. Silva-Rojas
et al.

Abstract: Tomato is the main vegetable cultivated under soilless culture systems (SCSs); production of organic tomato under SCSs has increased due to consumer demands for healthier and environmentally friendly vegetables. However, organic tomato production under SCSs has been associated with low crop performance and fruit quality defects. These agricultural deficiencies could be linked to alterations in tomato plant microbiota; nonetheless, this issue has not been sufficiently addressed. Thus, the main goal of the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 142 publications
0
3
0
Order By: Relevance
“…Meanwhile, the fungal composition in soil samples of the RC system was still different from that of the CC system and those of the CK shown in Figure 3F. The above results indicated that the rice-potato system could effectively modulate soil fungal community and promote the soilborne fungal diversity from a community scale in comparison with those of the CC system, which further validated that RC reshaped a more balanced fungal community [38][39][40] when combined with its much lesser enriched fungal taxa, thus, to effectively suppress the soilborne pathogens. However, when it comes to bacterial diversity, a diversified bacterial community does not denote soil health; for example, several studies concluded that higher bacterial diversity was associated with soil sickness [16,41].…”
Section: The Rice-potato Rotation System Could Promote the Fungal Spe...mentioning
confidence: 68%
“…Meanwhile, the fungal composition in soil samples of the RC system was still different from that of the CC system and those of the CK shown in Figure 3F. The above results indicated that the rice-potato system could effectively modulate soil fungal community and promote the soilborne fungal diversity from a community scale in comparison with those of the CC system, which further validated that RC reshaped a more balanced fungal community [38][39][40] when combined with its much lesser enriched fungal taxa, thus, to effectively suppress the soilborne pathogens. However, when it comes to bacterial diversity, a diversified bacterial community does not denote soil health; for example, several studies concluded that higher bacterial diversity was associated with soil sickness [16,41].…”
Section: The Rice-potato Rotation System Could Promote the Fungal Spe...mentioning
confidence: 68%
“…Alterations in the endophytic plant microbiome can render its destabilization, resulting in decreased crop yield and fruit quality, influenced by various factors such as fertilizer application, a detrimental factor [48]. In many instances, investigations into plant endophytic microbial communities unveil considerable taxonomic overlaps at the phylum level.…”
Section: Influence Of Glda-chelate Fertilization On Leaf and Root End...mentioning
confidence: 99%
“…It can be used on light and heavy soils of arable land at a dose of 20-40 t ha −1 . Brown coal waste of various grain sizes is used directly as a substrate for tomato [68,69], lettuce and cucumber [70,71], and ornamental plants [70] requiring continuous irrigation. By enriching BCW with super sorbents, a substrate that swells to different degrees when exposed to water is obtained.…”
Section: Use Of Brown Coal Waste In Cultivation Of Vegetablesmentioning
confidence: 99%